Production, Purification, and Characterization of Polygalacturonase from Rhizomucor pusillus Isolated from Decomposting Orange Peels. (17th October 2012) - Siddiqui, Mohd. Asif; Pande, Veena; Arif, Mohammad
Abstract : A thermophilic fungal strain producing polygalacturonase was isolated after primary screening of 40 different isolates. The fungus was identified as Rhizomucor pusilis by Microbial Type Culture Collection (MTCC), Chandigarh, India. An extracellular polygalacturonase (PGase) from R. pusilis was purified to homogeneity by two chromatographic steps using Sephadex G-200 and Sephacryl S-100. The purified enzyme was a monomer with a molecular weight of 32 kDa. The PGase was optimally active at 55°C and at pH 5.0. It was stable up to 50°C for 120 min of incubation and pH condition between 4.0 and 5.0. The stability of PGase decreases rapidly above 60°C and above pH 5.0. The apparentK m andV max values were 0.22 mg/mL and 4.34 U/mL, respectively. It was the first time that a polygalacturonase enzyme was purified in this species. It would be worthwhile to exploit this strain for polygalacturonase production. Polygalacturonase from this strain can be recommended for the commercial production because of its constitutive and less catabolically repressive nature, thermostability, wide range of pH, and lowerK m properties. However, scale-up studies are needed for the better output for commercial production.